The visual arts' role in the development of students' noosphere worldview - Nurke, Maira; Zhumabayeva, Aziya; Adenova, Lyazzat; Baikenova, Shaizada; Abilkalamova, Kamilya (Journal of Education and e-Learning Research, 2024)
Noospheric education is considered the basis for the formation of an environmental culture in people and society aimed at solving a complex of problems related to ensuring the sustainable development of society. Identifying promising areas for noospheric education development and demonstrating the importance of students developing a noospheric vision of the world through the visual arts depend on whether the necessary conditions for achieving the desired results have been established. This study aims to examine the impact of software on the effective formation of students' noospheric vision of the world using the visual arts. A quantitative and qualitative research design was used in this study. The study involved 240 fourth-grade students at secondary school no. 12 in the city of Almaty (Kazakhstan). The findings revealed issues with the formation of students' noospheric worldviews which demonstrates that students have an unstable perception of the intellectual sphere and develop an enthusiasm for the bright, spectacular objects and phenomena of their surroundings rather than their content. Experts can use the research findings to model environmental education in secondary schools, in the practical work of visual arts instructors, in the creation of curriculum and instructional aids for the visual arts and in the transmission of information on noospheric concepts.